2015
DOI: 10.1007/s13258-015-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ND1 gene mutation analysis in type II diabetes of Karaikudi population

Abstract: Mitochondrial single nucleotide polymorphisms (SNPs) are significantly correlated with the development of diabetes mellitus. However, these polymorphisms are emerging to be considerably diverse among different population and regions. Sivaganga district is recently being given importance for genetic studies due to its rigid family structure. Hence, the present study is planned to investigate the correlation between mitochondrial SNP of ND1 gene with type II diabetes (T2D) of Karaikudi population of Sivaganga di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The main objective of the study was to find out the role of demographic factors in the onset of diabetes and to detect their associated mutations in mitochondrial genes in a lesser known Mizo population. The prevalence of T2D rise with family history of diabetes and clinical representation depends mostly on the severity of insulinopenia, lack of physical activity, obesity, demographic factor and involvement of genetic factors [ 14 ]. From this study, the risk for T2DM was found to be higher in patients with high smoked meat consumption followed by excess smoking and alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the study was to find out the role of demographic factors in the onset of diabetes and to detect their associated mutations in mitochondrial genes in a lesser known Mizo population. The prevalence of T2D rise with family history of diabetes and clinical representation depends mostly on the severity of insulinopenia, lack of physical activity, obesity, demographic factor and involvement of genetic factors [ 14 ]. From this study, the risk for T2DM was found to be higher in patients with high smoked meat consumption followed by excess smoking and alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…A logistic regression analysis was carried out to calculate the influence of lifestyle and dietary factors for T2DM. Factors that were deemed of potential importance in the univariate analysis ( p < 0.05) were further analyzed in the multivariate analysis using Cox regression [ 22 ]. The independent effect of risk factors was investigated in a multivariate model (introducing all variables and terms of interactions) retaining the statistically significant factors which show a confounding effect only.…”
Section: Methodsmentioning
confidence: 99%